2018
DOI: 10.11604/pamj.2018.29.175.14101
|View full text |Cite
|
Sign up to set email alerts
|

Uterine torsion of 720 degrees in the third trimester of pregnancy and accompanying bladder torsion: a case report

Abstract: Partial rotation of the uterus not more than 45 degrees to the right is considered to be normal. Since all cases are not reported, the incidence of uterine torsion in pregnancy is not known exactly. In the literature, there have been reports of cases with uterine torsion ranging from 45 to 720 degrees. This is a case report of uterine torsion of 720 degrees with accompanying bladder torsion, developing after two caesarean sections, and developing of uterine atony after the operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…Diagnosis of uterine torsion is difficult with ultrasound alone. Suspicion for uterine torsion is usually seen when comparing previous ultrasounds and observing changes in anatomic location of pelvic structures 4–6. Our patient, unfortunately, did not have a prior ultrasound for comparison, and CT imaging plus laparotomy were used for diagnosis.…”
Section: Discussionmentioning
confidence: 86%
“…Diagnosis of uterine torsion is difficult with ultrasound alone. Suspicion for uterine torsion is usually seen when comparing previous ultrasounds and observing changes in anatomic location of pelvic structures 4–6. Our patient, unfortunately, did not have a prior ultrasound for comparison, and CT imaging plus laparotomy were used for diagnosis.…”
Section: Discussionmentioning
confidence: 86%
“…The operation was complicated by uterine atony and B lynch compression sutures were done. The patient was discharged home with her baby at day three postop [17]. Another case of 180 degrees uterine torsion happened in a preterm 30 weeks pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Myoma and pregnancy have adverse effects on each other, and the most serious effect is uterine torsion. [3][4][5] A study by Huang et al 6 revealed that the occurrence of uterine torsion in the third trimester of pregnancy may be correlated with an abnormal fetal position, older maternal age, and uterine ligament relaxation.…”
Section: Causes Of Uterine Torsion During Gestationmentioning
confidence: 99%